Strategi Komunikasi Bisnis Media Online Tribunbengkulu.com - Kendy, Komi; Narti, Sri; Murwani, Anis Endang Sri (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Competition among media is becoming increasingly fierce. An optimal business communication strategy is needed to grow and maintain existence. The purpose of this research is to understand the business strategies implemented by Tribunbengkulu.com, which is one of the local online media outlets in Bengkulu Province. The research was conducted using a qualitative descriptive research method. Data collection techniques were carried out through observation, interviews, and documentation. The theory used for analysis is the POAC theory. (Planning, Organizing, Actuating, Controlling). The research results show that the business strategy implemented by Tribunbengkulu.com is by strengthening the internal team and expanding the network of clients and readers in Bengkulu Province. (eksternal). Business communication at Tribunbengkulu.com has been going well, as it has positively impacted business revenue growth from 2022 to November 2024. To support the achievement, Tribunbengkulu.com has implemented the POAC model. At the planning stage, the business communication applied involves establishing internal communication strategies, as well as conducting external communication with advertising clients. At the organizing stage, the organization of communication at TribunBengkulu.com is evident from the clear hierarchy of task distribution instructions for each team, supported by adequate equipment resources. Internal communication is organized through faceto-face meetings or using applications that support real-time coordination among team members. Meanwhile, external communication is organized through business teams to manage interactions with advertising clients and editorial teams with the audience, ensuring that the messages conveyed are consistent. At the implementation stage (acting) at TribunBengkulu.com, it involves executing business communication plans, such as news publication, content production, content uploading, monitoring responses to reader comments, and handling advertising client needs. Internally, the implementation is carried out through team assignments. Externally, the implementation includes news promotion activities on social media, audience engagement management, and client services. Control is carried out through monitoring the content that has been produced and uploaded. TribunBengkulu.com uses analytics data to measure audience engagement on social media and the satisfaction level of advertising clients. At the internal level, feedback from employees and weekly or monthly performance reviews are used to assess the effectiveness of communication and make improvements if necessary. .